Study on hot deformation behavior of AISI 414 martensitic stainless steel using 3D processing map. (August 2020) - Chegini, M.; Aboutalebi, M.R.; Seyedein, S.H.; Ebrahimi, G.R.; Jahazi, M.
Abstract: Hot deformation of AISI 414 martensitic stainless steel was studied over the temperature and strain rate intervals of 950−1150 °C and 0.001 to 1 s −1, respectively. Based on the extracted data from hot compression tests a hyperbolic sine constitutive equation with correlation coefficient (R) of 0.99 was developed to model the flow behavior. The dynamic materials model (DMM) was used to establish the three-dimensional (3D) processing maps as a function of deformation temperature, strain rate, and strain. The analysis of the maps revealed that applied strain had a significant effect on power dissipation efficiency (η) and flow instability (ξ). Based on the generated processing maps four domains with the highest value of η were identified which represent the safe regions for hot working. Microstructural observation showed the significant effects of the temperature and strain rate on grain size evolution during hot deformation. From the microstructure analysis, the optimum hot working conditions were determined to be in the 1000−1130 °C temperature and 0.1–1 s −1 strain rate ranges. Dynamic recrystallization was identified as the dominant restoration mechanism under these conditions. The influence of carbides on size of the dynamic recrystallized grain was also studied and correlated with grain size evolution. On the basis of the obtained results, a correlation between the dynamically recrystallized grain size and Zener–Hollomon parameter is proposed.